Feedback Control of Injection Rate of the Injection Molding Machine Based on PID Improved by Unsaturated Integral. (25th May 2021) - Yang, An; Guo, Weigang; Han, Tianlong; Zhao, Congrong; Zhou, Hongwei; Cai, Jianping
Abstract : In conventional proportional–integral–derivative (PID) control, the integral term occupies a significant amount of controller memory, which prolongs the calculation time. The integral term easily leads to overshooting and oscillation, while the derivative term reduces the controller's anti-interference ability. In view of these problems, a PID expression with a recurrence relationship was derived, and the integral and differential terms of the conventional PID model were improved using an unsaturated integral and passivation differential to achieve a good control effect. Then, the improved PID was applied to the injection speed control of an injection molding machine, which is usually controlled using conventional PID control that featured difficulty in mathematical modeling, a nonlinear relationship between the input and the output, and high system complexity. Taking an injection molding machine as the control object, the transfer function of the injection system was constructed. Then, the improved PID was simulated using Matlab/Simulink. Lastly, the improved PID was verified using experiments. The simulation and the experimental results showed that the control model had a rapid response, no overshoot, and a high precision.